Compressive behaviour and environmental evaluation of sludge-derived masonry walls. (December 2021) - Liu, Yue; Zhuge, Yan; Chow, Christopher W.K.; Keegan, Alexandra; Li, Danda; Pham, Phuong Ngoc; Li, Luo
Abstract: The Paris Agreement, with its target of net-zero emissions by 2050, has forced the concrete industry to reduce its energy consumption and carbon emissions. Therefore, the development of green concrete with a lower environmental impact is urgently required. In this case study, alum sludge was used as both sand and cement replacement in concrete blocks, and the compressive behaviour of concrete blocks and constructed masonry walls was first investigated. For cement replacement, the strength of blocks decreased with increasing alum sludge ash (ASA) content when the cement replacement ratio was higher than 10% by weight. These results were attributed to the fact that the filler effect and pozzolanic reaction of ASA compensated for the cement dilution effect at a moderate replacement ratio. However, the cement dilution effect dominated the mechanism with further ASA addition. For sand replacement, 10% oven-dried alum sludge addition degraded the mechanical performance of blocks significantly due to high organic content, which might hinder cement hydration. The compression behaviour of masonry walls was also influenced by alum sludge, and the testing results showed that the sludge addition increased ductility of the masonry wall but decreased the strength insignificantly. Therefore, the sludge-derived blocks were suitable for masonry application. Furthermore, a life cycle assessment model was developed based on the designed sludge-derived cement supply chain in South Australia. The obtained results indicate that the annual reduced greenhouse gas emissions were around 1, 3339, 549 tons, which equaled to the amount of greenhouse gas released from 28, 898 passenger vehicles driven for a year. Highlights: Moderate replacement of cement exhibits no strength compromise. The strength of blocks decreases significantly when a moderate amount of sand is replaced with sludge. The addition of sludge decreased the stiffness but increased the ductility of masonry walls. Life cycle assessment confirms the significant contribution of recycling sludge for carbon neutrality.